Weak w2-stability and data dependence of Mann iteration method in Hilbert spaces - Guersoy, Faik; Khan, Abdul Rahim; Erturk, Muezeyyen; Karakaya, Vatan (SPRINGER-VERLAG ITALIA SRL, 2019)
We study a weaker and more natural notion of stability called weak w2-stability to get an insight in the corresponding results obtained by Mruter and Mruter (J Comput Appl Math 276:110-116, 2015) and Wang (J Comput Appl Math 285:226-229, 2015). A data dependence result for fixed points of strongly demicontractive operators is also established. Some illustrative examples are given to validate results obtained herein.
Keywords: Mann iteration; Strongly demicontractive operator; Data dependency; Stability; FIXED-POINTS; CONVERGENCE; EXISTENCE; OPERATORS; MAPPINGS; Mathematics; Science & Technology - Other Topics